Ethics and teaching innovation: a commitment within higher education management in Ecuador (Revista Innova Educación, 2023)
Introduction: At the present time, advances in science and technology have been directly reflected in educational processes at all levels, including higher education, a scenario in which values ​​such as ethics stand out, and the teaching commitment to continuous evolution. educational and cultural. Objective: The study carried out focused on highlighting the importance of ethical elements and teaching innovation within higher education management in Ecuador, since the "Citizen Revolution". Methodology: A documentary-bibliographic exploration was carried out, from which 75 articles related to the proposed theme were obtained, 32 being selected due to the exploration criteria, from the databases: EBSCO, Scielo, Redalyc, Dialnet, Science.gov and Redib, and published within the last five years. Results: Within the investigation it was possible to determine that there has been, since 2008, a series of restructurings, creations of laws and organisms, which, together with improvements in Ecuadorian higher education, have corrected very serious problems of the past, however, there is still a lack of professional updating and state-of-the-art equipment at the university level. Conclusions: Ethics is an essential element that must be included as a subject within the higher education curricula, as occurs in first world countries. With regard to innovation, the close link between ICTs and education is evident, fundamental components for quality educational training. Specifically, the case of Ecuador, there are advances, but not solid and structured enough, for the requirements of this society in continuous development.
Keywords: higher education; ethics; educational innovation; social values